1997
DOI: 10.1029/97jb02718
|View full text |Cite
|
Sign up to set email alerts
|

T waves from the great 1994 Bolivian deep earthquake in relation to channeling of S wave energy up the slab

Abstract: Abstract. We report the observation of T phases recorded at a number of Pacific island sites, following the great Bolivian deep earthquake of June 9, 1994. By studying their arrival times at the various stations, we unravel the process of conversion from seismic to acoustic energy at the South American coastline. We find that the maxima of amplitude of the phase are incompatible with propagation along the great circle from source to receiver but rather require the generation of the acoustic wave at a common po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 20 publications
3
22
0
Order By: Relevance
“…However, the results differ from those obtained by Talandier A detailed comparison of the results of this study with those of previous research shows that whether the T-waves were converted from P-or S-waves, they were consistently dependent on the incidence angles of the seismic waves. In the studies of both Okal and Talandier (1997) as well as in the present study, the seismic waves had an almost vertical incidence before being converted into T-waves, even though the seismic waves had been generated at different hypocentral distances. Consequently, the T-waves were converted from S-waves in both studies.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, the results differ from those obtained by Talandier A detailed comparison of the results of this study with those of previous research shows that whether the T-waves were converted from P-or S-waves, they were consistently dependent on the incidence angles of the seismic waves. In the studies of both Okal and Talandier (1997) as well as in the present study, the seismic waves had an almost vertical incidence before being converted into T-waves, even though the seismic waves had been generated at different hypocentral distances. Consequently, the T-waves were converted from S-waves in both studies.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, more detailed investigations into the conversion processes of acoustic energy (T-waves) from and to seismic waves based on the downslope conversion mechanism have been more numerous (Okal and Talandier, 1997;Talandier and Okal, 1998). For one, the T-phases that were generated by the great 1994 Bolivian deep earthquake and recorded at a number of Pacific island sites significantly corresponded to the arrivals of regional S-waves at the conversion points (Okal and Talandier, 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By exploiting these characteristics, regional hydroacoustic arrays can provide significant improvements in detection threshold and location accuracy, relative to land-based seismic monitoring (Fox et al 1994;. Importantly, T-wave studies have done much to define mid-ocean ridge eruptive processes (e.g., Fox et al 1995;Dziak and Fox 1999), illuminate the complex structure of subduction zones and slabs (e.g., Fox and Dziak 1999;Okal and Talandier 1997), provide insights into transform fault dynamics (e.g., Dziak et al 1997;McGuire et al 2005) and shown great promise as a tool in addressing a variety of other tectonic problems (e.g., Smith et al 2002;Bohnenstiehl et al 2002Escartín et al 2003).…”
Section: Introduction To Hydroacoustic Methodsmentioning
confidence: 98%
“…For example, an earthquake generated signal which propagates through the ocean and is then recorded on a T-phase station might have been called``PTP''. The problem with this approach is that the mode of propagation on land is not known and probably includes compressional, shear and surface type waves (PISERCHIA et al, 1998;OKAL and TALANDIER, 1997;STEVENS et al, 1998). It would be similar to separating the regional seismic Lg phase into its various components.…”
Section: T H and N Phasesmentioning
confidence: 99%